The Disaster of Literacy: Prevention of News Forwarding Tendencies on Social Media - Anwar, Anwar; Suzana, ‪Yenny (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
One of the indicators of insufficient literacy knowledge in society is their susceptibility to deal with conflict, hate speech, hoax, and defamation. This article represents research findings aimed at exploring the literacy skills of the academic community of IAIN Langsa in accepting disastrous information on news that leads to harmful and misleading content. Moreover, it also aimed at disseminating preventive information for not forwarding news obtained from social media, which is used as a medium of information, to reduce the disaster risks that trigger a moral loss in society. This research applied descriptive methods. The research subjects were students, lecturers, and staff of IAIN Langsa. Data were collected using a questionnaire via Google form and semi-structured interviews.